PENGARUH PROMOSI TERHADAP PEMANFAATAN PERPUSTAKAAN DI PERPUSTAKAAN UNIVERSITAS PGRI PALEMBANG - Susi Marlina (Perpustakaan Nasional RI, 2017)
This research was conducted in PGRI Library of Palembang, the purpose of this research is to know the influence of promotion to library utilization and also to know promotion activity and library utilization activity in PGRI Palembang University Library, this research is expected to be useful for all reading community or for researcher , And beneficial to University of Palembang PGRI librarian, as well as for other researchers. In this study, the main problem is 1). How is the library promotion activities at the Library of Teachers' Union University of Indonesia (PGRI) Palembang? 2). What are the activities of library utilization in the Library of Teachers' Union of the Republic of Indonesia (PGRI) of Palembang? 3) .Is there any influence of promotion on library utilization in Palembang University Teachers Association (PGRI) Library Palembang? The type of research used by researchers is quantitative and supported by qualitative data. Quantitative data in question is the relationship between promotion with library utilization. Analysis of data used is to use product moment correlation statistics. From result of hypothesis test, there is a significant influence between promotion with library utilization by student, on calculation with product moment correlation obtained alue equal to 0,819 while table with N = 31 at significant/eve/ R5% and R1% (0,202 0,819 0,148). The result shows that the better promotion available in the library, the higher the interest of visit and the utilization of the library by the students.